PENGARUH PERSEPSI KEMANFAATAN, PERSEPSI KEMUDAHAN DAN KEPUASAN PENGGUNA TERHADAP MINAT MEMBAYAR PAJAK BUMI DAN BANGUNAN (PBB) MENGGUNAKAN SHOPEEPAY - Siti Sainang; Andri Waskita Aji (Universitas Muhammadiyah Makassar, 2021)
This study aims to examine the effect of perceived usefulness, perceived convenience and user satisfaction on interest in paying PBB using shopeepay. This research method uses quantitative description methods and primary data using questionnaires. The population in this study are Shopeepay users and are Land and Building Taxpayers of Sleman Regency with a sample of 100. and analyzed using smartPLS. The sampling technique used was convenience sampling technique. Data retrieval is done by distributing questionnaires in the form of a google form. The results of this smartPLS test result that perceived usefulness has a positive effect on interest in paying PBB using shopeepay. Easy perception also has a positive effect on interest in paying PBB using shopeepay. And user satisfaction has a positive effect on interest in paying PBB using shopeepay.